Penerapan Quality Function Deployment Untuk Pengembangan Produk Perajang Bawang - Sakti, Arya Mahendra (Department Industrial Engineering, University of Muhammadiyah Malang, 2007)
This research was expected to apply QFD in the development process of product which refers to consumer request, so that the result of scheme process really answers market requirement. The research methods were conducting product survey in field, making questionaire of consumer request, spreading questioner, checking returned questioner data, and the processing questioner data by QFD. The matrix of concept assessment shows that concept A (funnel one semi automatic) gets value 0.238 and 16510%; concept B (funnel two semi automatic) gets value 0.211 and 16630%; concept C (funnel two semi automatic/manual) gets value 0.203 and 18470%; so that amongst the third concept, the one which is appropriate to be proceeded to the production department is only concept A.